The Dutch Revolt and Catholic exile in Reformation Europe - Janssen, Geert H.; Cambridge eBooks (Cambridge : Cambridge University Press, 2014)
The Dutch Revolt of the sixteenth century sparked one of the largest refugee crises of Reformation Europe. This book explores the flight, exile and eventual return of Catholic men and women during the war. By mapping the Catholic diaspora across Europe, Geert Janssen explains how exile worked as a catalyst of religious radicalisation and transformed the world views, networks and identities of the refugees. Like their Protestant counterparts, the displaced Catholic communities became the mobilising forces behind a militant International Catholicism. The Catholic exile experience thus facilitated the permanent separation of the northern and southern Netherlands. Drawing on diaries, letters and evidence from material culture, this book offers a penetrating picture of the lives of early modern refugees and their agency in the Counter-Reformation.
List of Governors-General in the Low Countries, 1559-1609 -- Introduction -- PART I. FLIGHT -- Corpus Christianum divided -- Exodus -- PART II. EXILE -- Conditions of displacement -- The Counter-Reformation of the refugee -- International Catholicism -- PART III. RETURN -- A new order : the southern Netherlands -- Negotiating diversity : the Dutch Republic -- Epilogue.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Catholic Church -- Netherlands -- History; Reformation -- Netherlands; Catholics -- Religious identity -- Netherlands -- History; Religious refugees -- Netherlands -- History; Counter-Reformation -- Netherlands; Electronic books